Spectrum of psychotic disorder in patients presenting with first-episode psychosis at tertiary care hospital, Karachi - Iqbal, Fariha; Afridi, Muhammad Iqbal (Journal of Pakistan Psychiatric Society, 2019)
OBJECTIVE: To determine the frequency of spectrum of psychotic disorder in patients presenting with first-episode psychosis, admitted in a Tertiary Care Hospital, Karachi.METHODS: A prospective cross-sectional study was conducted at the Department of Psychiatry, Jinnah Postgraduate Medical Center (JPMC), Karachi, in August 2016 (the patients previously admitted from 1st January 2015 to 31st December 2015 were contacted). Spectrum of psychotic disorders which were previously diagnosed and labelled using International Classification of Diseases (ICD-10) were included in the study.RESULT: Out of 124 patients meeting the inclusion criteria, 52 (41.9%) were males and 72 (58.1%) were females. Amongst the patients with first episode psychosis it was found that 12.9% had schizophrenia, 29% had acute and transient psychotic disorder, 37.9% had bipolar affective disorder, 10.5% had substance use disorder, 4% had depressive disorder with psychotic features, 1.6% had organic delusional disorder and 4% had mental and behavioral disorder associated with puerperium.CONCLUSION: First psychotic episode has a diverse psychopathology where majority of patients had bipolar affective disorder with psychotic features and warrants timely recognition and management.